Analisa dan Perancangan Sistem Informasi Stock Kontrol Berintegrasi dengan Manajemen Keuangan Pada Permata - Sularno, Sularno; Mulya, Dio Prima (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
Rapid technological developments have brought us to coexist with the information and the technology itself. Today many people have left the process of manually tracking information that takes a long time to find the data, now many companies are turning to use a computerized system so that we can access information quickly and accurately. Cellular gem Sawahan Padang is one of the distributors of various brands of mobile phones, accessories, pulses and diecast in downtown Padang. As time goes by Gem Holiday growing rapidly, the demand for the product is increasing. At the company's common stock ignorance goods, goods to be sold as well as its financial management is not sufficiently organized in the absence of information on the use of computerized systems that have not. Based on the existing difficulties, the authors tried to develop the above system using a database in the storage, data processing is easy and more accurate data resulting in faster time